Building Nationalism Through War History - Wiyono, Wujud; Udayana, Agung (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
History education has an important role in forming nationalism and love for the homeland. After Indonesian independence, history education was transformed into a tool for building nationalism. The focus of history teaching now includes the struggle for independence, important events in Indonesian history, and the values ​​of togetherness and national unity. Through tracing the course of history, one can understand the struggles and achievements that shaped their homeland. The study of history also encourages active participation in efforts to advance the country and fosters love for the homeland. The spirit of nationalism is a sense of pride in one's identity as an Indonesian citizen, which is reflected in the priority given to the collective interests of the nation above all else. The history of Indonesian independence inspired this attitude, with heroes who fought with a nationalist spirit. It is hoped that history education will be able to teach students that in the current context, the expression of nationalism is no longer shown through resistance to colonialism or efforts to achieve independence, but rather on how we can maintain and express love for our homeland.